1995
DOI: 10.1523/jneurosci.15-04-02961.1995
|View full text |Cite
|
Sign up to set email alerts
|

ATP causes release of intracellular Ca2+ via the phospholipase C beta/IP3 pathway in astrocytes from the dorsal spinal cord

Abstract: Calcium signaling within astrocytes in the CNS may play a role comparable to that of electrical signaling within neurons. ATP is a molecule known to produce Ca2+ responses in astrocytes, and has been implicated as a mediator of intercellular Ca2+ signaling in other types of nonexcitable cells. We characterized the signal transduction pathway for ATP-evoked Ca2+ responses in cultured astrocytes from the dorsal spinal cord. Nearly 100% of these astrocytes respond to extracellularly applied ATP, which causes rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(95 citation statements)
references
References 75 publications
7
86
0
2
Order By: Relevance
“…For A23187 and thapsigargin experiments, drugs were applied by bath in the extracellular recording solution. As described previously in detail (Salter and Hicks, 1995), excitation light was generated from a 75 W xenon arc lamp and passed alternatingly through 340 or 380 nm bandpass filters (Omega Optical). The emitted light was directed through a 510 nm bandpass filter and the light collected by a photomultiplier tube detector.…”
Section: Methodsmentioning
confidence: 99%
“…For A23187 and thapsigargin experiments, drugs were applied by bath in the extracellular recording solution. As described previously in detail (Salter and Hicks, 1995), excitation light was generated from a 75 W xenon arc lamp and passed alternatingly through 340 or 380 nm bandpass filters (Omega Optical). The emitted light was directed through a 510 nm bandpass filter and the light collected by a photomultiplier tube detector.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that the plateau may predominantly result from entry of extracellular Ca 2+ . When C6 glioma cells were preincubated with U73122, which is a potent inhibitor of both ΡΙΧβ and PLCy [22,12], the hypo-osmolarity-induced [Ca 2+ ]; response was preserved (Fig. 2C).…”
Section: Activation Of Erk-1 and Erk-2 And Occurrence Of Mobility-shimentioning
confidence: 99%
“…Purinoceptors have been classified into three main subgroups, adenosine/P1, ionotropic P2X, and metabotropic P2Y receptors (P2XR and P2YR), which differ in their pharmacological profiles, transduction mechanisms, and molecular structures (Ralevic and Burnstock, 1998). These purinoceptor subtypes distribute differentially to neurons and glial cells throughout the mammalian CNS, including the cerebellum and other brain areas (Evans et al, 1992;Kirischuk et al, 1995;Salter and Hicks, 1995;North and Barnard, 1997;Mateo et al, 1998;North, 2002). Previous studies have shown that activation of adenosine/P1 receptors elicits presynaptic and postsynaptic inhibitory actions on central and peripheral synapses.…”
Section: Introductionmentioning
confidence: 99%